Improving creative thinking of high school students through chemistry teaching:Thesis for master degree of chemistry teaching: 60 14 01 11 - Mai, Thị Nhàn (Trường Đại học giáo dục, 2017)
M.A. Thesis Theory and teaching methodology of chemistry -- University of Education. Vietnam National University, Hanoi, 2015